2022
DOI: 10.1093/nar/gkac764
|View full text |Cite
|
Sign up to set email alerts
|

sgcocaller and comapr: personalised haplotype assembly and comparative crossover map analysis using single-gamete sequencing data

Abstract: Profiling gametes of an individual enables the construction of personalised haplotypes and meiotic crossover landscapes, now achievable at larger scale than ever through the availability of high-throughput single-cell sequencing technologies. However, high-throughput single-gamete data commonly have low depth of coverage per gamete, which challenges existing gamete-based haplotype phasing methods. In addition, haplotyping a large number of single gametes from high-throughput single-cell DNA sequencing data and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Hidden Markov Model (HMM) was used to phase the hetSNPs and 99.97% of the hetSNPs were precisely phased to the correct haplotype in the genome (Supplementary Table S1 ), which was comparable with previous studies. The SNP linkage in the gametes offers information for constructing chromosome-level phased haplotypes of the individual 25 . Then, we inferred crossovers on each chromosome of every single sperm with the phased haplotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Hidden Markov Model (HMM) was used to phase the hetSNPs and 99.97% of the hetSNPs were precisely phased to the correct haplotype in the genome (Supplementary Table S1 ), which was comparable with previous studies. The SNP linkage in the gametes offers information for constructing chromosome-level phased haplotypes of the individual 25 . Then, we inferred crossovers on each chromosome of every single sperm with the phased haplotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al developed Hapi, which utilizes sperm data to obtain haplotypes by employing the PHMM (pairwise Hidden Markov Model) method 23 . Lyu et al developed sgcocaller software, which outperforms the Hapi algorithm in accuracy and performance, providing great efficiency for sperm research 24 . In this study, we sequenced 102 sperm cells with an average depth of 10.05X and sequenced the blood samples from the donor boar with 95.12X, which allowed us to directly infer sperm haplotypes, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The inference accuracies for 4-gamete, 5-gamete, and 6-gamete analyses were also 100%, as displayed in We demonstrated that IIIandMe, which applies to genomic data of high quality, can accurately infer chromosomal haplotypes using three or a few more single gametes and is computationally much more efficient than Hapi. Given that crossovers are very rare (Beye et al 2006;Lyu et al 2022), three gametes are theoretically sufficient for phasing the entire genome, likely pushing the boundary to its possible limit. We foresee that IIIandMe will find its way to become impactful in many genetic research areas and applications.…”
mentioning
confidence: 99%